Relokasi cedera sendi bahu anterior dengan metode kocher - Roy Januardi Irawan, (Ilmu Keolahragaan, 2013)
The shoulder joint is the most easier joint which got injured, especially in sports that predominantly using arm swing such as badminton, tennis, volley ball, etc. But there were many other sports type could injured the shoulder joint which caused by an collision withanother object. One of the injured type is shoulder joint dislocation. When the dislocation happened on athletes, the RICE method is the first aid for reduce the pain or avoid the Injured getting worst. One of method to relocate the shoulder joint dislocation was Kochers method. This article will discuss about shoulder joint dislocation using Kochers Method.   Key Word:  Anterior Shoulder dislocation, Kochers method